Lithium-containing phosphate cathode material, preparation method and application
Patent Information
- Application Number
- CN202611139817.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-16
AI Technical Summary
[0002]磷酸铁锂因其高安全、长循环和低成本优势成为锂离子电池主流正极材料,但在低温环境下,由于锂离子一维扩散通道的本征缺陷、电解液黏度剧增以及电荷转移阻抗急剧上升,导致容量衰减严重,室温下约10-¹4~10-¹6cm²/s的扩散系数在-20℃进一步下降2~4个数量级,成为制约其在电动汽车和储能领域推广应用的关键瓶颈
本申请中含锂磷酸盐正极材料大孔的孔体积占总孔体积的60%-85%,大孔作为锂离子快速运输的主干道及电解液的储存库,大孔的孔容占比在该范围内利于锂离子的快速运输、并具有足够的储液空间,可提升材料低温容量保持率。
Smart Images

Figure CN122930906A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cathode material technology, and more specifically, to lithium phosphate cathode materials, their preparation methods, and their applications. Background Technology
[0002] Lithium iron phosphate (LiFePO4) has become the mainstream cathode material for lithium-ion batteries due to its high safety, long cycle life, and low cost. However, at low temperatures, due to intrinsic defects in the one-dimensional diffusion channels of lithium ions, a sharp increase in electrolyte viscosity, and a rapid rise in charge transfer impedance, its capacity decays significantly, reaching approximately 10 μL at room temperature. - ¹ 4 ~10 - ¹ 6 The diffusion coefficient of cm² / s decreases by 2 to 4 orders of magnitude at -20℃, becoming a key bottleneck restricting its widespread application in electric vehicles and energy storage.
[0003] Existing methods for improving low-temperature performance cannot fundamentally improve the macroscopic transport efficiency of ions within the electrode channels.
[0004] In view of this, the present invention is proposed. Summary of the Invention
[0005] The purpose of this invention is to provide lithium phosphate cathode materials, preparation methods and applications, and to improve the low-temperature performance of lithium phosphate cathode materials.
[0006] This invention is implemented as follows: In a first aspect, the present invention provides a lithium phosphate cathode material, wherein the pore volume of the macropores in the lithium phosphate cathode material accounts for 60%-85% of the total pore volume, wherein the total pore volume is the sum of the volumes of pores with a diameter of 2-5000 nm, and the volume of the macropores is the sum of the volumes of pores with a diameter of 200-5000 nm.
[0007] In an optional embodiment, the volume of the macropore is 0.20-0.35 cm³. 3 / g; And / or, the pore size distribution diagram of the lithium phosphate cathode material tested by mercury intrusion porosimetry includes a first peak and a second peak, and the peak height ratio of the first peak to the second peak is 1-12; optionally, the peak height ratio of the first peak to the second peak is 1.5-7.
[0008] In an optional embodiment, the lithium phosphate cathode material comprises secondary particles composed of primary particles, wherein the secondary particles are spherical or near-spherical. And / or, the total pore volume of the lithium phosphate cathode material is 0.25-0.5 cm³. 3 / g; And / or, the D50 of the lithium phosphate cathode material is 4-15 μm; And / or, the tap density of the lithium phosphate-containing cathode material is 1.2-1.7 g / cm³. 3 ; And / or, the lithium phosphate cathode material includes doping elements, and the doping amount of the doping elements in the lithium phosphate cathode material is 1000-8000ppm; And / or, the lithium phosphate cathode material includes a doping element selected from at least one of magnesium, aluminum, titanium, niobium and zirconium; And / or, the lithium phosphate cathode material includes a lithium phosphate cathode material matrix and a carbon coating layer that at least partially covers the lithium phosphate cathode material matrix, wherein the mass fraction of the carbon coating layer in the lithium phosphate cathode material is 0.5-5%.
[0009] In a second aspect, the present invention provides a method for preparing the lithium phosphate cathode material according to any one of the foregoing embodiments, comprising: spray drying a mixed slurry including an iron source, a phosphorus source, a lithium source, a carbon source and a solvent to obtain a dried powder; The dried powder is sintered under a protective atmosphere to obtain the lithium phosphate cathode material.
[0010] In an optional embodiment, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium phosphate, lithium acetate, lithium sulfate, lithium nitrate, and lithium chloride. And / or, the iron source is selected from at least one of ferric phosphate, ferric oxide, ferrous oxalate, and iron(II,III) oxide; And / or, the phosphorus source is selected from at least one of iron phosphate, ammonium dihydrogen phosphate, phosphoric acid, lithium dihydrogen phosphate, lithium phosphate, and ethylenediaminetetramethylenephosphoric acid; And / or, the carbon source is selected from at least one of glucose, sucrose, maltose, citric acid, polyacrylamide, polyacrylic acid, polyvinyl alcohol and polyethylene glycol; And / or, the mixture slurry further includes additives selected from at least one of manganese phosphate, manganese carbonate, magnesium acetate, alumina, titanium dioxide, niobium pentoxide and zirconium oxide; And / or, the solvent is selected from deionized water or anhydrous ethanol.
[0011] In an optional embodiment, the molar ratio of Li in the lithium source to P in the phosphorus source is 0.99-1.03:1; And / or, the iron source and the phosphorus source are iron phosphate, and the mass ratio of the carbon source to the iron phosphate is (0.05-0.2):1.
[0012] In an optional embodiment, the D50 of the solids in the mixed slurry is 150-300 nm; And / or, the solid content of the mixed slurry is 25-40%; And / or, the atomization method of the spray drying is two-fluid atomization; And / or, the spray pressure of the spray dryer is 0.3-0.8 MPa; the inlet air temperature is 180-280℃; and the outlet air temperature of the spray dryer is 95-110℃. And / or, the D50 of the dried powder is 5-12 μm; And / or, the sintering includes a first-stage sintering and a second-stage sintering, wherein the first-stage sintering temperature is 400-500℃ and the holding time is 1-3h; and the second-stage sintering temperature is 720-760℃ and the holding time is 12-18h. And / or, the heating rate of the sintering step is 1-3℃ / min.
[0013] In an optional embodiment, the lithium source is selected from lithium carbonate; And / or, the carbon source is selected from a mixture of glucose and polyethylene glycol; And / or, the additive is selected from titanium dioxide; And / or, the solvent is selected from deionized water; And / or, the molar ratio of Li in the lithium source to P in the phosphorus source is 1.00-1.02:1; And / or, the D50 of the solids in the mixed slurry is 180-250 nm; And / or, the solid content of the mixed slurry is 30-35%; And / or, the spray pressure of the spray dryer is 0.35-0.60 MPa, the inlet air temperature is 230-250℃, and the outlet air temperature is 95-105℃; And / or, the D50 of the dried powder is 6-10 μm.
[0014] Thirdly, the present invention provides an electrode sheet comprising the lithium phosphate cathode material described in any one of the foregoing embodiments.
[0015] Fourthly, the present invention provides a lithium-ion battery comprising the electrode sheet described in the foregoing embodiments.
[0016] The present invention has the following beneficial effects: In this application, the pore volume of the lithium phosphate cathode material is 60%-85% of the total pore volume. As the main channel for the rapid transport of lithium ions and the storage tank for electrolyte, the pore volume ratio of macropores within this range is conducive to the rapid transport of lithium ions and has sufficient liquid storage space, which can improve the low-temperature capacity retention rate of the material. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 The pore size distribution of the lithium phosphate cathode material prepared in Example 1; Figure 2 The pore size distribution is shown in Example 3 for the lithium phosphate cathode material prepared. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0020] This invention provides a lithium phosphate cathode material, wherein the pore volume of the macropores in the lithium phosphate cathode material accounts for 60%-85% of the total pore volume, wherein the total pore volume is the sum of the volumes of pores with a diameter of 2-5000 nm, and the volume of the macropores is the sum of the volumes of pores with a diameter of 200-5000 nm.
[0021] In the lithium phosphate cathode material provided in this application, the pores (macropores) of 200-5000 nm can serve as electrolyte reservoirs and rapid transport channels. The pore volume of the macropores in the lithium phosphate cathode material accounts for 60%-85% of the total pore volume, for example, 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 75%, 76%, 78%, 80%, 82%, 84%, and 85%, ensuring that the total proportion of macropores is moderate. That is, the macropores serve as the main channels for rapid lithium-ion transport and electrolyte reservoirs. The pore volume proportion of macropores within this range is conducive to the rapid transport of lithium-ions and provides sufficient liquid storage space, which can improve the low-temperature capacity retention rate of the material.
[0022] In an optional embodiment, the volume of the macropore is 0.20-0.35 cm³. 3 / g, such as 0.200 cm³ / g, 0.230 cm³ / g, 0.250 cm³ / g, 0.261 cm³ / g, 0.272 cm³ / g, 0.283 cm³ / g, 0.294 cm³ / g, 0.305 cm³ / g, 0.316 cm³ / g, 0.327 cm³ / g, 0.338 cm³ / g, and 0.350 cm³ / g, are beneficial for maintaining the tap density of the material while improving the low-temperature capacity retention rate.
[0023] In an optional embodiment, the pore size distribution map of the lithium phosphate cathode material, tested by mercury intrusion porosimetry, includes a first peak and a second peak, with a peak height ratio of 1-12; for example, 1, 1.5, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12. In this application, the peak height ratio of the first peak to the second peak is obtained by mercury intrusion porosimetry. The pore size distribution map shows two peaks in the range of 20-5000 nm, where the first peak represents the ordinate of the peak with a pore size in the range of 200-5000 nm, and the second peak represents the ordinate of the peak with a pore size in the range of 20-200 nm. By adjusting the peak height ratio of the first peak to the second peak to the above range, the pores in the 20-5000 nm range are kept open and continuous, providing a better path for lithium ion transport at low temperatures.
[0024] In an optional implementation, the peak height ratio of the first peak to the second peak is 1.5-7.
[0025] In an optional implementation, the peak height ratio of the first peak to the second peak is 1.5-5.
[0026] In an optional embodiment, the lithium phosphate cathode material comprises secondary particles composed of primary particles, wherein the secondary particles are spherical or near-spherical.
[0027] In an optional embodiment, the total pore volume of the lithium phosphate cathode material is 0.25-0.5 cm³. 3 / g, for example, 0.25cm 3 / g, 0.27cm 3 / g, 0.30cm 3 / g, 0.32cm 3 / g, 0.34cm 3 / g, 0.35cm 3 / g, 0.40cm 3 / g, 0.42cm 3 / g, 0.45cm 3 / g, 0.47cm 3 / g, 0.48cm 3 / g, 0.5cm 3 / g.
[0028] The pore volume of the total pores within a suitable range, combined with the proportion of the macropore volume, is more conducive to improving the low-temperature retention rate of the material.
[0029] In an optional embodiment, the D50 of the lithium phosphate cathode material is 4-15 μm, for example 4.0 μm, 5.2 μm, 6.4 μm, 7.6 μm, 8.8 μm, 10.0 μm, 11.2 μm, 12.4 μm, 13.6 μm, 14.8 μm, and 15.0 μm.
[0030] In an optional embodiment, the BET of the lithium phosphate cathode material is 5-12m. 2 / g, such as 5.0 m² / g, 5.8 m² / g, 6.6 m² / g, 7.4 m² / g, 8.2 m² / g, 9.0 m² / g, 9.8 m² / g, 10.6 m² / g, 11.4 m² / g, 12.0 m² / g.
[0031] In an optional embodiment, the lithium phosphate cathode material includes a doping element, and the doping amount of the doping element in the lithium phosphate cathode material is 1000-8000 ppm, for example 1000 ppm, 1800 ppm, 2600 ppm, 3400 ppm, 4200 ppm, 5000 ppm, 5800 ppm, 6600 ppm, 7400 ppm, or 8000 ppm.
[0032] In an optional embodiment, the lithium phosphate cathode material includes a doping element selected from at least one of manganese, magnesium, aluminum, titanium, niobium, and zirconium.
[0033] In an optional embodiment, the lithium phosphate cathode material includes titanium. Trace amounts of titanium incorporated into the lattice of the lithium phosphate cathode material can partially replace Fe sites, thereby reducing the Li content by modulating the local crystal field. + The migration energy barrier in the bulk phase, combined with the macroporous structure, can further optimize low-temperature performance.
[0034] In an optional embodiment, the lithium phosphate cathode material includes a lithium phosphate cathode material matrix and a carbon coating layer that at least partially covers the lithium phosphate cathode material matrix. The mass fraction of the carbon coating layer in the lithium phosphate cathode material is 0.5-5%, for example, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, or 5.0%.
[0035] A carbon coating with a mass fraction of 0.5–5% can improve conductivity while retaining ion diffusion channels, which is beneficial for improving low-temperature performance.
[0036] The present invention also provides a method for preparing the lithium phosphate cathode material according to any one of the foregoing embodiments, comprising: spray drying a mixed slurry including an iron source, a phosphorus source, a lithium source, a carbon source, an additive and a solvent to obtain a dried powder; The dried powder is sintered under a protective atmosphere to obtain the lithium phosphate cathode material.
[0037] The method for preparing lithium phosphate cathode material of this application can achieve a pore volume of macropores accounting for 60%-85% of the total pore volume in the lithium phosphate cathode material, which significantly improves the low-temperature capacity retention of the lithium phosphate cathode material.
[0038] In an optional embodiment, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium phosphate, lithium acetate, lithium sulfate, lithium nitrate and lithium chloride; preferably, the lithium source is selected from lithium carbonate.
[0039] In an optional embodiment, the iron source is selected from at least one of ferric phosphate, ferric oxide, ferrous oxalate, and ferric oxide.
[0040] In an optional embodiment, the phosphorus source is selected from at least one of iron phosphate, ammonium dihydrogen phosphate, phosphoric acid, lithium dihydrogen phosphate, lithium phosphate, and ethylenediaminetetramethylenephosphoric acid.
[0041] In an optional embodiment, the carbon source is selected from at least one of glucose, sucrose, maltose, citric acid, polyacrylamide, polyacrylic acid, polyvinyl alcohol, and polyethylene glycol; preferably, the carbon source is selected from a mixture of glucose and polyethylene glycol.
[0042] In an optional embodiment, the additive is selected from at least one of manganese phosphate, manganese carbonate, magnesium acetate, aluminum oxide, titanium oxide, niobium pentoxide and zirconium oxide; preferably, the additive is selected from titanium oxide.
[0043] In an optional embodiment, the solvent is selected from deionized water or anhydrous ethanol; preferably, the solvent is selected from deionized water.
[0044] In an optional embodiment, the molar ratio of Li in the lithium source to P in the phosphorus source is 0.99-1.03:1, for example, 0.990:1, 0.994:1, 0.998:1, 1.002:1, 1.006:1, 1.010:1, 1.014:1, 1.018:1, 1.022:1, or 1.030:1; preferably, the molar ratio of Li in the lithium source to P in the phosphorus source is 1.00-1.02:1; this is beneficial for reducing lithium-deficient phases (FePO4) or lithium-rich impurities (Li3PO4), ensuring the purity of the main phase and the stability of the voltage plateau, and reducing interfacial side reactions.
[0045] In an optional embodiment, the iron source and the phosphorus source are iron phosphate, and the mass ratio of the carbon source to the iron phosphate is (0.05-0.2):1, for example, 0.050:1, 0.067:1, 0.083:1, 0.100:1, 0.117:1, 0.133:1, 0.150:1, 0.167:1, 0.183:1, or 0.200:1; preferably, the mass ratio of the carbon source to the iron phosphate is 0.08-0.16:1.
[0046] In an optional embodiment, the D50 of the solids in the mixed slurry is 150-300 nm, for example, 150 nm, 167 nm, 183 nm, 200 nm, 217 nm, 233 nm, 250 nm, 267 nm, 283 nm, or 300 nm; preferably, the D50 of the solids in the mixed slurry is 180-250 nm.
[0047] In an optional embodiment, the solid content of the mixed slurry is 25-40%, for example 25%, 27%, 29%, 31%, 33%, 35%, 37%, 39%, 40%; preferably, the solid content of the mixed slurry is 30-35%.
[0048] In an optional embodiment, the atomization method of the spray drying is two-fluid atomization.
[0049] In an optional embodiment, the spray pressure for spray drying is 0.3-0.8 MPa, for example 0.30 MPa, 0.36 MPa, 0.41 MPa, 0.47 MPa, 0.52 MPa, 0.58 MPa, 0.63 MPa, 0.69 MPa, 0.74 MPa. MPa, 0.80MPa; inlet air temperature is 180-280℃, for example 180℃, 191℃, 202℃, 213℃, 224℃, 235℃, 246℃, 257℃, 268℃, 279℃, 280℃; the outlet air temperature of the spray dryer is 95-110℃, for example 95℃, 97℃, 99℃, 101℃, 103℃, 105℃, 107℃, 109℃, 110℃; preferably, the spray pressure of the spray dryer is 0.35-0.60MPa, the inlet air temperature is 230-250℃, and the outlet air temperature is 95-105℃.
[0050] Adjusting the atomization parameters of the two fluids and the spray drying conditions is beneficial for the stable preparation of secondary agglomerates with uniform particle size and good sphericity. After high-temperature sintering, lithium phosphate cathode materials with target pore size distribution and interconnected channels can be obtained. In an optional embodiment, the D50 of the dried powder is 5-12 μm, for example, 5.0 μm, 5.8 μm, 6.6 μm, 7.4 μm, 8.2 μm, 9.0 μm, 9.8 μm, 10.6 μm, 11.4 μm, or 12.0 μm; preferably, the D50 of the dried powder is 7-10 μm; more preferably, 7-10 μm. This particle size window can both prevent excessively fine particles from agglomerating and causing a decrease in packing efficiency due to frictional resistance, and prevent excessively coarse particles from causing an extended diffusion path of the electrolyte within the cathode material.
[0051] In an optional embodiment, the sintering includes a single-stage sintering and a two-stage sintering. The single-stage sintering temperature is 400-500℃, for example, 400℃, 411℃, 422℃, 433℃, 444℃, 455℃, 466℃, 477℃, 488℃, 499℃, or 500℃, and the holding time is 1-3 hours, for example, 1.0 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours, 2.0 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, or 3.0 hours. The two-stage sintering temperature is 720-760℃, for example, 720℃, 724℃, 729℃, 733℃, 738℃, 742℃, 747℃, 751℃, 756℃, or 760℃, and the holding time is 12-18 hours, for example, 12.0 hours or 12.7 hours. h, 13.3 h, 14.0 h, 14.7 h, 15.3 h, 16.0 h, 16.7 h, 17.3 h, 18.0 h.
[0052] In an optional embodiment, the heating rate of the sintering step is 1-3℃ / min, for example 1.0℃ / min, 1.2℃ / min, 1.4℃ / min, 1.6℃ / min, 1.8℃ / min, 2.0℃ / min, 2.2℃ / min, 2.4℃ / min, 2.6℃ / min, 2.8℃ / min, or 3.0℃ / min, which is beneficial for the stability of the large-pore skeleton.
[0053] The present invention also provides an electrode sheet comprising the lithium phosphate cathode material described in any one of the foregoing embodiments.
[0054] The present invention also provides a lithium-ion battery, including the electrode sheet described in the foregoing embodiments.
[0055] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0056] Example 1 This embodiment provides a method for preparing a lithium phosphate-containing cathode material, the preparation method of which is as follows: (1) Li2CO3 was used as the lithium source, FePO4 as the iron and phosphorus sources, TiO2 as the additive, and glucose and PEG as the carbon sources. The lithium source, phosphorus source, and iron source were prepared according to the molar ratio of Li:P:Fe of 1.01:1:0.970; the mass fraction of glucose was 10wt% of FePO4, the mass fraction of PEG was 5wt% of FePO4, and TiO2 was added with a theoretical titanium content of 3500ppm in LFP. The materials were dispersed in a quantitative amount of deionized water for 30min. (2) Pour the mixed slurry into a sand mill and grind it to obtain a ground slurry. Control its D50 to 0.20μm to obtain a slurry with a solid content of 30%. (3) The above slurry was spray-dried using a two-fluid spray dryer with the atomizing air pressure controlled at 0.40 MPa, the inlet air temperature at 240℃ and the outlet air temperature at 100℃ to obtain a dried powder with a particle size D50 of 9.5 μm. (4) The dried powder was sintered in a furnace filled with an inert atmosphere at a heating rate of 2°C / min. The temperature was first raised to 460°C and held for 2 hours, then raised to 740°C and held for 15 hours. The furnace was then allowed to cool naturally to room temperature to obtain the lithium phosphate cathode material. Figure 1 This is a pore size distribution diagram for pore sizes ranging from 200 to 5000 nm obtained by mercury intrusion porosimetry.
[0057] Example 2 This embodiment provides a method for preparing a lithium phosphate cathode material, which differs from Example 1 in steps (1), (2), and (3); the specific conditions are as follows: (1) The lithium source, phosphorus source, and iron source were prepared according to a molar ratio of Li:P:Fe of 1.005:1:0.970; the mass fraction of glucose was 8 wt% of FePO4 and the mass fraction of PEG was 5 wt% of FePO4. (2) Control the D50 of the grinding slurry to 0.25μm to obtain a slurry with a solid content of 30%; (3) Spray drying with the air inlet temperature controlled at 230℃ and the air outlet temperature controlled at 110℃ to obtain dry powder with a particle size D50 of 7.32μm.
[0058] Example 3 This embodiment provides a method for preparing a lithium phosphate cathode material, which differs from Example 1 in steps (2), (3), and (4); the specific conditions are as follows: (2) Control the D50 of the grinding slurry to 0.25μm to obtain a slurry with a solid content of 30%; (3) Spray drying with the air inlet temperature controlled at 230℃ and the air outlet temperature at 100℃ to obtain dried powder with a particle size D50 of 8.61μm; (4) The dried powder is sintered in a furnace filled with an inert atmosphere at a heating rate of 2°C / min. The temperature is first raised to 460°C and held for 2 hours, then raised to 740°C and held for 12 hours. The furnace is then allowed to cool naturally to room temperature to obtain the lithium phosphate cathode material product. Figure 2 This is a pore size distribution diagram for pore sizes ranging from 200 to 5000 nm obtained by mercury intrusion porosimetry.
[0059] Example 4 This embodiment provides a method for preparing a lithium phosphate cathode material, which differs from Example 1 in step (4); the specific conditions are as follows: (4) The dry powder is sintered in a furnace filled with an inert atmosphere at a heating rate of 2°C / min. The temperature is first raised to 460°C and held for 2 hours, then raised to 760°C and held for 15 hours. The furnace is then allowed to cool naturally to room temperature to obtain the lithium phosphate cathode material.
[0060] Example 5 This embodiment provides a method for preparing a lithium phosphate cathode material, which differs from Example 1 in steps (1), (2), and (3); the specific conditions are as follows: (1) The lithium source, phosphorus source, and iron source were prepared according to a molar ratio of Li:P:Fe of 1.005:1:0.970; the mass fraction of glucose was 8 wt% of FePO4 and the mass fraction of PEG was 8 wt% of FePO4. (2) Control the D50 of the grinding slurry to 0.25μm to obtain a slurry with a solid content of 30%; (3) Spray drying is performed with the atomizing pressure controlled at 0.50 MPa, the inlet air temperature at 230℃ and the outlet air temperature at 110℃ to obtain dried powder with a particle size D50 of 6.35 μm.
[0061] Example 6 This embodiment provides a method for preparing a lithium phosphate cathode material, which differs from Example 1 in steps (2) and (3); the specific conditions are as follows: (2) Controlling the D50 of the mixed slurry to 0.25 μm, a slurry with a solid content of 35% was obtained; (3) The above slurry was sprayed using a two-fluid spray dryer with the atomizing air pressure controlled at 0.40 MPa, the inlet air temperature at 240°C, and the outlet air temperature at 100°C to obtain a dried powder with a particle size D50 of 7.87 μm.
[0062] Example 7 This embodiment provides a method for preparing a lithium phosphate cathode material, which differs from Example 1 in step (4); the specific conditions are as follows: (4) The dry powder is sintered in a furnace filled with an inert atmosphere at a heating rate of 1℃ / min. First, the temperature is raised to 460℃ and held for 2 hours, then the temperature is raised to 740℃ and held for 15 hours. The furnace is then allowed to cool naturally to room temperature to obtain the lithium phosphate cathode material.
[0063] Comparative Example 1 This comparative example provides a method for preparing a lithium phosphate cathode material, which differs from Example 1 in steps (1) and (2); the specific conditions are as follows: (1) The lithium source, phosphorus source, and iron source were prepared according to a molar ratio of Li:P:Fe of 1.005:1:0.970; the mass fraction of glucose was 8 wt% of FePO4 and the mass fraction of PEG was 5 wt% of FePO4. (2) Pour the mixed slurry into a sand mill and grind it to obtain a ground slurry. Control its D50 to 0.50 μm to obtain a slurry with a solid content of 45%. (3) The above slurry was sprayed using a two-fluid spray dryer, with the atomizing air pressure controlled at 0.40 MPa, the inlet air temperature at 240°C, and the outlet air temperature at 100°C to obtain a dried powder with a particle size D50 of 11.62 μm.
[0064] Comparative Example 2 This comparative example provides a method for preparing a lithium phosphate cathode material. The difference from Example 1 lies in step (4), and the specific conditions are as follows: (4) The dry powder is sintered in a furnace filled with an inert atmosphere at a heating rate of 5°C / min. The temperature is first raised to 460°C and held for 2 hours, then raised to 740°C and held for 15 hours. The furnace is then allowed to cool naturally to room temperature to obtain lithium phosphate cathode material.
[0065] Comparative Example 3 The difference between this comparative example and Example 1 is that it uses a conventional commercial lithium phosphate cathode material.
[0066] Test method: 1. 200-5000nm pore size distribution test method: The pore size was measured by mercury intrusion porosimetry (MIP) using a Micron AutoPore IV 9500 instrument. The pressure range was 0.5-33000psi, the pore size range was 360.48μm-5.48nm, and the test environment temperature was 24℃. Pores with a diameter >5000nm were determined to be invalid deposited pores based on the peak shape and actual material properties and were excluded.
[0067] 2. 2-200nm pore size distribution test method: The specific test was conducted using the Micromeritics TriStar II Plus surface area and pore size analyzer. The specific test process is as follows: After the sample was degassed and weighed, it was loaded into the analysis station. Nitrogen gas was used as the adsorbate at liquid nitrogen temperature. The software was set to BJH mode and the relative pressure point (P / P0 0.02~0.99) was set. The instrument automatically measured the adsorption-desorption isotherm.
[0068] 3. Tap density test method: The tap density is determined by a powder tap density tester, referring to the national standard GB / T5162-2021 Determination of tap density of metal powder.
[0069] 4. Particle size Dv50: Determined by a laser particle size analyzer (instrument model: Mastersizer3000) in accordance with the national standard GB / T 19077-2024 Particle size analysis by laser diffraction.
[0070] 5. Electrochemical Testing Method: The positive electrode material from the above examples and comparative examples was mixed with conductive carbon black, binder PVDF (polyvinylidene fluoride) in a ratio of 90:5:5 with solvent NMP to form a slurry. This slurry was then coated onto aluminum foil to form the positive electrode sheet. A lithium metal sheet was used as the negative electrode sheet. The battery casing, positive and negative electrode sheets, separator, spring contacts, and gaskets were assembled into a coin cell in a vacuum glove box. A Blue Electric testing system was used to perform a 0.2C charge test at room temperature (2.0-3.75V) followed by a 0.2C discharge test at -20℃ (the specific capacity used for current calculation was 160mAh g⁻¹).
[0071] Table 1. Pore volume and peak height ratio of cathode materials
[0072] Table 2 Physicochemical data and electrochemical properties of cathode materials
[0073] As can be seen from the table above, in Comparative Examples 1 and 3, the volume of the macropores accounts for a relatively low proportion of the total pore volume, and the low-temperature capacity retention rate is less than 60%; in Comparative Example 2, the volume of the macropores accounts for too high a proportion, and the low-temperature capacity retention rate is also lower than that of the examples.
[0074] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A lithium phosphate cathode material, characterized in that, The macropore volume of the lithium phosphate cathode material accounts for 60%-85% of the total pore volume, wherein the total pore volume is the sum of the volumes of pores with a diameter of 2-5000 nm, and the macropore volume is the sum of the volumes of pores with a diameter of 200-5000 nm.
2. The lithium phosphate cathode material according to claim 1, characterized in that, The volume of the large hole is 0.20-0.35 cm³. 3 / g; And / or, the pore size distribution diagram of the lithium phosphate cathode material tested by mercury intrusion porosimetry includes a first peak and a second peak, and the peak height ratio of the first peak to the second peak is 1-12; optionally, the peak height ratio of the first peak to the second peak is 1.5-7.
3. The lithium phosphate cathode material according to claim 1, characterized in that, The lithium phosphate cathode material includes secondary particles composed of primary particles, and the secondary particles are spherical or near-spherical. And / or, the total pore volume of the lithium phosphate cathode material is 0.25-0.5 cm³. 3 / g; And / or, the D50 of the lithium phosphate cathode material is 4-15 μm; And / or, the tap density of the lithium phosphate cathode material is 1.2-1.7 g / cm³. 3 ; And / or, the lithium phosphate cathode material includes doping elements, and the doping amount of the doping elements in the lithium phosphate cathode material is 1000-8000ppm; And / or, the lithium phosphate cathode material includes a doping element selected from at least one of manganese, magnesium, aluminum, titanium, niobium and zirconium; And / or, the lithium phosphate cathode material includes a lithium phosphate cathode material matrix and a carbon coating layer that at least partially covers the lithium phosphate cathode material matrix, wherein the mass fraction of the carbon coating layer in the lithium phosphate cathode material is 0.5-5%.
4. A method for preparing the lithium phosphate cathode material according to any one of claims 1-3, characterized in that, include: A mixed slurry containing iron, phosphorus, lithium, carbon and solvent is spray-dried to obtain a dried powder. The dried powder is sintered under a protective atmosphere to obtain the lithium phosphate cathode material.
5. The method for preparing the lithium phosphate cathode material according to claim 4, characterized in that, The lithium source is selected from at least one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium phosphate, lithium acetate, lithium sulfate, lithium nitrate, and lithium chloride. And / or, the iron source is selected from at least one of ferric phosphate, ferric oxide, ferrous oxalate, and iron(II,III) oxide; And / or, the phosphorus source is selected from at least one of iron phosphate, ammonium dihydrogen phosphate, phosphoric acid, lithium dihydrogen phosphate, lithium phosphate, and ethylenediaminetetramethylenephosphoric acid; And / or, the carbon source is selected from at least one of glucose, sucrose, maltose, citric acid, polyacrylamide, polyacrylic acid, polyvinyl alcohol and polyethylene glycol; And / or, the mixed slurry further includes additives selected from at least one of manganese phosphate, manganese carbonate, magnesium acetate, alumina, titanium dioxide, niobium pentoxide and zirconium oxide; And / or, the solvent is selected from deionized water or anhydrous ethanol.
6. The method for preparing the lithium phosphate cathode material according to claim 4, characterized in that, The molar ratio of Li in the lithium source to P in the phosphorus source is 0.99-1.03:1; And / or, the iron source and the phosphorus source are iron phosphate, and the mass ratio of the carbon source to the iron phosphate is (0.05-0.2):
1.
7. The method for preparing the lithium phosphate cathode material according to claim 4, characterized in that, The solids in the mixed slurry have a D50 of 150-300 nm; And / or, the solid content of the mixed slurry is 25-40%; And / or, the atomization method of the spray drying is two-fluid atomization; And / or, the spray pressure of the spray dryer is 0.3-0.8 MPa; the inlet air temperature is 180-280℃; and the outlet air temperature of the spray dryer is 95-110℃. And / or, the D50 of the dried powder is 5-12 μm; And / or, the sintering includes a first-stage sintering and a second-stage sintering, wherein the first-stage sintering temperature is 400-500℃ and the holding time is 1-3h; and the second-stage sintering temperature is 720-760℃ and the holding time is 12-18h. And / or, the heating rate of the sintering step is 1-3℃ / min.
8. The method for preparing the lithium phosphate cathode material according to claim 5, characterized in that, The lithium source is selected from lithium carbonate; And / or, the carbon source is selected from a mixture of glucose and polyethylene glycol; And / or, the additive is selected from titanium dioxide; And / or, the solvent is selected from deionized water; And / or, the molar ratio of Li in the lithium source to P in the phosphorus source is 1.00-1.02:1; And / or, the D50 of the solids in the mixed slurry is 180-250 nm; And / or, the solid content of the mixed slurry is 30-35%; And / or, the spray pressure of the spray dryer is 0.35-0.60 MPa, the inlet air temperature is 230-250℃, and the outlet air temperature is 95-110℃; And / or, the D50 of the dried powder is 6-10 μm.
9. An electrode sheet, characterized in that, Includes the lithium phosphate cathode material as described in any one of claims 1-3.
10. A lithium-ion battery, characterized in that, Includes the electrode sheet as described in claim 9.